Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

(3y+2)(y–1) simplify??

Sagot :

Answer:

  • [tex]\boxed{\sf{3y^2-y-2}}[/tex]

Step-by-step explanation:

Given:

Isolate the term of y from one side of the equation.

(3y+2)(y-1)

Use the foil method.

[tex]\underline{\text{FOIL METHOD:}}[/tex]

[tex]\Longrightarrow: \sf{\left(A+B\right)\left(C+D\right)=AC+AD+BC+BD}[/tex]

(3y+2)(y-1)=3yy+3y(-1)+2y+2(-1)

Solve.

[tex]\sf{3yy=3y^2}\\\\\\\sf{3y(-1)=-3y}\\\\\\\sf{2(-1)=-2}[/tex]

[tex]\sf{3y^2-3y+2y-2}[/tex]

Add or subtract the numbers from left to right.

Solutions:


[tex]\sf{-3y+2y=-y}[/tex]

[tex]\Longrightarrow: \boxed{\sf{3y^2-y-2}}[/tex]

  • Therefore, the correct answer is 3y²-y-2.

I hope this helps. Let me know if you have any questions.

Answer:

3y^2-y-2

Step-by-step explanation:

(3y+2)(y–1)

Use the FOIL method

First 3y * y = 3y^2

outer  3y * -1 = -3y

inner  2 * y = 2y

last  2 * -1 = -2

Add them together

3y^2 -3y +2y -2

Combine like term

3y^2-y-2